NIAT KONSUMEN MEMBELI ULANG PRODUK MEWAH SMARTPHONE - Core, Claudia Lorenzia; Suprapti, Ni Wayan Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.06.TAHUN 2018, 2018)
This study aims to examine the factors that influence the intention of Denpasar city consumers to repurchase the iPhone brand smartphone products, namely consumer inertia, luxury value, product attributes, customer satisfaction and social aspects. The study also tested the effect of customer satisfaction mediation on the relationship between product attributes and re-purchase intentions, as well as the role of moderator of social aspects of the relationship between consumer inertia and repurchase intentions. Respondents who participated in this study as many as 154 people who meet the sample criteria that are domiciled in Denpasar city, have graduated high school and are using smartphone brand iPhone. The results showed that consumer inertia has no effect on repurchase intention. It was further discovered that product attributes were a key driver of customer satisfaction and repurchase intentions. Customer satisfaction is also found to mediate the relationship between product attributes and repurchase intentions. In addition to product attributes, the luxury value found to be able to encourage repurchase intention as well as social aspects strengthens the relationship between consumer inertia and repurchase intentions.